Differential effects of adolescent health behaviours on adult cardiometabolic health by parental and neighbourhood socioeconomic background - Jackisch, Josephine; Noor, Nazihah; Raitakari, Olli T; Lehtimäki, Terho; Kähönen, Mika; Cullati, Stéphane; Delpierre, Cyrille; Kivimäki, Mika; Carmeli, Cristian (Oxford University Press (OUP), 2026)
Adolescent healthy behaviours may improve cardiometabolic health in adulthood differently across socioeconomic groups. We aimed to quantify the effects of adolescent healthy behaviours on multiple biomarkers of adult cardiometabolic health by socioeconomic backgrounds. We used a population-based cohort of Finnish adolescents from the Young Finns Study (1980–89, n = 2984) followed into adulthood (2001–11). Healthy behaviours (no smoking, no alcohol consumption, sufficient physical activity, daily fruit and vegetable consumption) and socioeconomic backgrounds (parental- and neighbourhood-related) were measured in adolescence (12–18 years). Biomarkers of adiposity [waist circumference, body mass index (BMI)], cardiovascular [blood pressure (BP), cholesterol, apolipoprotein B], and metabolic [plasma glucose, insulin resistance] outcomes were measured in adulthood (33–40 years). We estimated conditional average effects of healthy behaviours via inverse-probability-weighted marginal structural models. Sufficient physical activity lowered adiposity biomarkers to a greater extent among adolescents from disadvantaged neighbourhood, with additional decreases of 2.2 cm [95% confidence interval (CI): −0.1 to 4.7] in waist circumference and 1 kg/m2 (95% CI: 0.2 to 1.9) in BMI. In contrast, daily fruit and vegetable consumption lowered BP with additional 2.0–3.6 mmHg (95% CI: 0.3 to 6.1) among adolescents with advantaged either parental or neighbourhood socioeconomic backgrounds. There was little evidence for differential effects on other outcomes and for no smoking and alcohol. Socioeconomic backgrounds modified the effects of adolescent physical activity and fruit and vegetable consumption on adult cardiometabolic health. These findings indicate that population-wide interventions promoting healthy behaviours during adolescence have the potential to either mitigate or exacerbate long-term socioeconomic inequalities in cardiometabolic health.